Penggunaan multimedia interaktif untuk meningkatkan keterampilan pemecahan masalah geometri peserta didik kelas v sekolah dasar - Rohmat Nur Udin; Riyadi Riyadi; Sukarno Sukarno (Universitas Sebelas Maret, 2023)
The purpose of the research is to remind the problem solving skills of geometry task using interactive multimedia. Interactive multimedia presented as an alternative to boosting learners' understanding from abstract to concrete. Class action research consists of 2 cycles. The implementation of class action research are 4 stages including: 1) planning; 2) implementation; 3) observation; 4) reflection. The research subject of grade V students at SDN Soropadan in the 2019/2020 school year. Data collection techniques in this research is form of interviews, observations, and tests. The result of pre-act problem solving skills showed 0%. Cycle 1 at meeting 1 68%, at meeting 2 54% classically. The next research in cycle 2 at meetings 1 86%, at meetings 2 100% classically. The actions of each meeting in the cycle increase the percentage of problem solving skills achievment. The implementation of interactive multimedia can improve the problem solving skills about geometry tasks.